Moving Toward Climate Budgeting : Policy Note - World Bank Group (Washington, DC, 2014)
Climate change action by countries - both mitigation measures and adaptation measures requires planning over a long horizon in the face of uncertainty as well as, for many governments, costly financing in the near term. While flows of international climate finance have grown in recent years, it has become ever clearer that countries need to consider all policy instruments. Climate change is going to affect, in particular, the core business of finance ministries related to fiscal policy, government budgets, and public debt. This note focuses on public expenditure management for climate actions rather than the full spectrum of finance ministry responsibilities. Climate change planning shares some common challenges with other national policy objectives where multiple interests need to be managed - but also presents some unique complexities. This policy note presents several measures of immediate interest to finance ministries for better fiscal planning and expenditure management of climate actions. Drawing on the sourcebook, climate change public expenditure and institutional review, the note highlights three general areas of financial and expenditures management where improved practice will better prepare finance ministries to deal with the fiscal implications of climate change: (i) including climate change as a long-term objective in the national budget and expenditure framework; (ii) improving financial tracking and performance accountability by spending agencies; and (iii) strengthening government financial management systems to efficiently use external climate finance. Targeted at the climate budget, these actions will also promote financial discipline and overall lead to more efficient and strategic public spending. This policy note provides finance officials with seven detailed recommendations based on the experience of World Bank client countries.